Airborne LiDAR acquisition, post-processing and accuracy-checking for a 3D WebGIS of Copan, Honduras. (February 2016) - von Schwerin, Jennifer; Richards-Rissetto, Heather; Remondino, Fabio; Spera, Maria Grazia; Auer, Michael; Billen, Nicolas; Loos, Lukas; Stelson, Laura; Reindel, Markus
Abstract: Archaeological projects increasingly collect airborne LiDAR data to use as a remote sensing tool for survey and analysis. Publication possibilities for LiDAR datasets, however, are limited due to the large size and often proprietary nature of the data. Fortunately, web-based, geographic information systems (WebGIS) that can securely manage temporal and spatial data hold great promise as virtual research environments for working with and publishing LiDAR data. To test this and to obtain new data for archaeological research, in 2013, the MayaArch3D Project (www.mayaarch3d.org ) collected LiDAR data for the archaeological site of Copan, Honduras. Results include: 1) more accurate archaeological maps, 2) identification of unrecorded archaeological features, 3) an assessment of combining LiDAR and ground-checking to increase data accuracy in ecologically and topographically diverse landscapes, and 4) new LiDAR datasets that are hosted in a 3D WebGIS and integrated with other archaeological data to enhance data accessibility and collaborative research. Highlights: 25 km 2 of LiDAR were collected at Copan to improve existing maps. LiDAR improves accuracy of, and also is checked by, legacy data (ground surveys). Previously unmapped ancient structures and terraces were identified at Copan. Automated approaches assist analysis; visual analysis & ground checks still crucial. 3D WebGIS integrates LiDAR data and archaeological data for collaborative research.